Evaluation of Space And Plant Selection to Create A Sustainable Home Yard in Legian Village: Evaluasi Ruang dan Pemilihan Tanaman Guna Menciptakan Halaman Rumah Lestari di Kelurahan Legian - Agung Ayu Wulandira Sawitri Djelantik, Anak; Wayan Febriana Utami, Ni; Kohdrata, Naniek; Fitriani, Yuyun; Komang Wahyu Utama Tirta, I; Bagus Damar Putra, Ida; Ayu Karunia Dewani, Luh; Gusti Ayu Agung Jaya Purnamasari, I (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The problem of limited green open space in densely populated areas such as Legian Village requires the optimal utilization of home yards. Through the Udayana Mengabdi Program, this activity aimed to enhance community knowledge and skills in managing home yards to provide ecological, aesthetic, health, and even economic value. The implementation included counseling, discussions, and field practice with resource persons from landscape architecture and agroecotechnology. The materials covered residential garden design, the use of narrow land, and the cultivation of aesthetic plants such as orchids. The results showed an increase in residents’ understanding of home green space planning, appropriate plant selection based on land conditions, and awareness of the health and psychological benefits of gardening. In addition, the community was able to design home yards not only as green spaces but also as sources of added value for their families. Overall, the program successfully encouraged Legian residents to manage their yards creatively, functionally, and sustainably, thereby contributing to improved environmental quality, health, and community well-being.